Pengaruh Transparansi Pengelolaan Pajak Dan Keadilan Pajak Terhadap Kepercayan Wajib Pajak Pada Kpp Pratama Tangerang Timur Tahun 2020 - Agus Maulani; Novianita Rulandari; Rahardi Pratomo (Jurnal Ilmu Administrasi Publik, 2021)
This research was conducted in Pratama East Tangerang Tax Service Office (KPP), and was intended to gain insight on how tax management transparency andtax equity affects taxpayers' trust. This was a quantitative research and the data was gathered through survey analysis. The research sample was taxpayers of KPP Pratama East Tangerang, from which there were 100 respondents. The data was then analyzed using multiple linear regression. The writer used SPSS 25 for this research. The results showed that Tax Management Transparency (X1) did not significantly affect Taxpayers' Trust (Y) towards KPP Pratama, East Tangerang— 21 ,9%— and the rest (78, 1%) was affected by other factors outside the scope of this research that was not further researched by the writer. Tax Equity (X2) also did not significantly affect Taxpayers' Trust (Y) towards KPP Pratama, East Tangerang, by only 28,4%; the rest (71 ,6%) was affected by other factors outside the scope of this research that was not further researched by the writer. The last, both Tax Management Transparency (X1) and Tax Equity (X2) did not significantly affect Taxpayers' Trust (Y) towards KPP Pratama, East Tangerang, by only 32,7%; the rest (67,3%) was affected by other factors outside the scope of this research that was not further researched by the writer.